026 Gene-environment interactions in multiple sclerosis: a UK Biobank study. Issue 6 (27th May 2022) - Jacobs, Benjamin; Noyce, Alastair; Bestwick, Jonathan; Belete, Daniel; Giovannoni, Gavin; Dobson, Ruth
Abstract : Question: Does genetic risk modify the effect of environmental MS risk factors? Methods: Case-control study of 2151 people with MS and 486, 125 controls using data from a longitudinal cohort (UK Biobank). MS was defined using ICD-coding or self-report. Associations with MS risk were quan- tified using multivariate logistic regression. Interaction between environmental and genetic risk factors was quantified using the Attributable Proportion due to interaction (AP). Model fits were quantified using Nagelkerke's pseudo-R2 metric. Results: Exposures associated with MS were childhood obesity (OR=1.39, 95%CI 1.22–1.58), smoking (OR=1.19, 95%CI 1.07–1.33), and earlier menarche 0.95, 95%CI 0.92–0.98). The autosomal polygenic risk score (PRS) was associated with MS disease status (ORTop-vs-bottom-decile=3.93, 95%CI 3.11–4.97). There was evidence of synergistic interaction between the PRS and both childhood obesity (AP=0.111, 95%CI 0.007–0.202), and smoking (AP=0.106, 95%CI 2.24e-4 to 0.196). Conclusions: We provide novel evidence for interaction between environmental risk factors for MS and a high burden of autosomal genetic risk. These findings have significant implications for our understanding of MS biology, and may inform targeted prevention strategies. ben.meir.jacobs@gmail.com